2016
DOI: 10.1002/tox.22234
|View full text |Cite
|
Sign up to set email alerts
|

In vitro profiling of toxicity and endocrine disrupting effects of bisphenol analogues by employing MCF‐7 cells and two‐hybrid yeast bioassay

Abstract: The potentially adverse health implications of bisphenol A (BPA) have led to increasing use of alternative bisphenols (BPs). However, little is known about the toxicity of alternative BPs. In this study, the cytotoxicity, genotoxicity, intracellular ROS formation, and Ca fluctuation effects of BPs on MCF-7 cells were evaluated. At the same time, the estrogenic and thyroidal hormone effect potentials of six BPs were also evaluated using two-hybrid yeast bioassay. The results showed that most BPs at 0.01-1 μM si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 50 publications
2
22
1
Order By: Relevance
“…Although the chemical structures of BPA and its analogues are similar, HCA demonstrated differential adverse effects of 4 bisphenols on multiple molecular and cellular events, suggesting that different mechanisms may promote cytotoxicity. Similar findings were reported in previous in vitro studies, in which BPAF and TBBPA showed higher endocrine modulating potentials in human MCF7 breast cancer cells and Leydig cells, respectively, as compared with BPA (Lei et al, 2016;Roelofs et al, 2015). BPS showed similar inhibitory effects with BPA on testosterone secretion in human fetal testes and induced more sensitive responses in mice testes (Eladak et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Although the chemical structures of BPA and its analogues are similar, HCA demonstrated differential adverse effects of 4 bisphenols on multiple molecular and cellular events, suggesting that different mechanisms may promote cytotoxicity. Similar findings were reported in previous in vitro studies, in which BPAF and TBBPA showed higher endocrine modulating potentials in human MCF7 breast cancer cells and Leydig cells, respectively, as compared with BPA (Lei et al, 2016;Roelofs et al, 2015). BPS showed similar inhibitory effects with BPA on testosterone secretion in human fetal testes and induced more sensitive responses in mice testes (Eladak et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to perturbing the ER pathway, BPAF and BPC have been reported to interact with other endocrine targets (Delfosse et al, 2014;Grimaldi et al, 2019;Lei et al, 2017;Wang et al, 2014). The increasing and widespread use of these bisphenol analogues and their ability to interact with endocrine molecular targets at lower concentrations than BPA pose a serious concern associated with potential health risks for humans and wildlife.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Rachoń 2015). The bisphenols are EDCs known to act through the estrogen receptors (ERs) to regulate downstream signaling and gene expression responses (Lei et al. 2017; Li et al.…”
Section: Introductionmentioning
confidence: 99%